The Adaptive Characteristics of Cholesterol and Bile Acid Metabolism in Nile Tilapia Fed a High-Fat Diet. (24th November 2022) - Li, Rui-Xin; Qian, Yi-Fan; Zhou, Wen-Hao; Wang, Jun-Xian; Zhang, Yan-Yu; Luo, Yuan; Qiao, Fang; Chen, Li-Qiao; Zhang, Mei-Ling; Du, Zhen-Yu
Abstract : Since high-fat diet (HFD) intake elevates liver cholesterol and enhanced cholesterol-bile acid flux alleviates its lipid deposition, we assumed that the promoted cholesterol-bile acid flux is an adaptive metabolism in fish when fed an HFD. The present study investigated the characteristic of cholesterol and fatty acid metabolism in Nile tilapia ( Oreochromis niloticus ) after feeding an HFD (13% lipid level) for four and eight weeks. Visually healthy Nile tilapia fingerlings (average weight 3.50 ± 0.05   g ) were randomly distributed into four treatments (4-week control diet or HFD and 8-week control diet or HFD). The liver lipid deposition and health statue, cholesterol/bile acid, and fatty acid metabolism were analyzed in fish after short-term and long-term HFD intake. The results showed that 4-week HFD feeding did not change serum alanine transaminase (ALT) and aspartate transferase (AST) enzyme activities, along with comparable liver malondialdehyde (MDA) content. But higher serum ALT and AST enzyme activities and liver MDA content were observed in fish fed 8-week HFD. Intriguingly, remarkably accumulated total cholesterol (mainly cholesterol ester, CE) was observed in the liver of fish fed 4-week HFD, along with slightly elevated free fatty acids (FFAs) and comparable TG contents. Further molecular analysis in the liver showed that obvious accumulation of CE and total bile acids (TBAs) in fish fed 4-week HFD was mainly attributed to the enhancement of cholesterol synthesis, esterification, and bile acid synthesis. Furthermore, the increased protein expressions of acyl-CoA oxidase 1/2 (Acox1 and Acox2), which serve as peroxisomal fatty acid β -oxidation (FAO) rate-limiting enzymes and play key roles in the transformation of cholesterol into bile acids, were found in fish after 4-week HFD intake. Notably, 8-week HFD intake remarkably elevated FFA content (about 1.7-fold increase), and unaltered TBAs were found in fish liver, accompanied by suppressed Acox2 protein level and cholesterol/bile acid synthesis. Therefore, the robust cholesterol-bile acid flux serves as an adaptive metabolism in Nile tilapia when fed a short-term HFD and is possibly via stimulating peroxisomal FAO. This finding enlightens our understanding on the adaptive characteristics of cholesterol metabolism in fish fed an HFD and provides a new possible treatment strategy against metabolic disease induced by HFD in aquatic animals.